Computational fluid dynamics evaluation of posterior septectomy as a viable treatment option for large septal perforations. Issue 7 (23rd May 2017) - Otto, Bradley A.; Li, Chengyu; Farag, Alexander A.; Bush, Benjamin; Krebs, Jillian P.; Hutcheson, Ryan D.; Kim, Kanghyun; Deshpande, Bhakthi; Zhao, Kai
Abstract : Background: Numerous surgical techniques exist to treat nasal septal perforation (NSP). The surgical closure of large NSPs (>2 cm) is still challenging. Posterior septectomy has been reported as a simple alternative to treat large NSP, yet its mechanisms for symptom relief are not clear, and if failed, its consequence cannot be easily reversed. Methods: Ten NSP patients were recruited: 5 underwent posterior septectomy and 5 underwent conventional flap or button repair. Computational fluid dynamics (CFD) simulated the nasal aerodynamics based on computed tomography (CT) scans. All patients had preoperative CT; however, only 4 had postoperative CT: 2 underwent posterior septectomy and the other 2 underwent flap repair. We examined surgical outcomes and the nasal airflow features among the 2 treatment options. Results: Both groups of patients had good outcomes based on chart review. Patients undergoing septectomy had significantly larger perforation size (2.32 ± 0.87 vs 1.21 ± 0.60 cm), higher flow rate across the perforation (47.8 ± 28.6 vs 18.3 ± 12.2 mL/second), and higher wall shear stress (WSS) along the posterior perforation margin (1.39 ± 0.52 vs 1.15 ± 0.58 Pa). The posterior WSS significantly correlated with crossover flow velocity ( r = 0.77, p = 0.009) and was reduced by almost 67% postseptectomy, and by 29% postrepair. Conclusion: This is the first CFD analysis on an NSP patient cohort. NSP resulted in flow disturbance and increased WSS that potentially led to symptomatology. The removal of high stress points along the posterior margin may explain why posterior septectomy can be an effective treatment option. Aerodynamic abnormalities, in addition to perforation size and location, could serve as basis for future treatment decisions.